The Exchange Rate System : Lessons of the Past and Options for the Future. (Occasional Papers; Occasional Paper ;, 1984)
The last few years have witnessed a resurgence of calls for a re-examination, or perhaps even a reform, of the international monetary system. This paper contributes to the ongoing debate on that subject in three ways: 1 it suggests a set of criteria for evaluating alternative exchange rate systems; 2 it provides a comprehensive appraisal of a decade of experience with the present exchange rate system in terms of those criteria; and 3 it selects some key issues as a basis for discussion on how the evolution of the exchange rate system might best be managed over the medium term.